Raytracing atmospheric delays in ground-based GNSS reflectometry - Nikolaidou, T.; Santos, M. C.; Williams, S. D. P.; Geremia-Nievinski, F. (Journal of geodesy, 2020)
Several studies have recognized that Global Navigation Satellite System Reflectometry (GNSS-R) is subject to atmospheric propagation delays. Unfortunately, there is little information in the peer-reviewed literature about the methods and algorithms involved in correcting for this effect. We have developed an atmospheric ray-tracing procedure to solve rigorously the three-point boundary value problem of ground-based GNSS-R observations. We defined the reflection-minus-direct or interferometric delay in terms of vacuum distance and radio length. We clarified the roles of linear and angular refraction in splitting the total delay in two components, along-path and geometric. We have introduced for the first time two subcomponents of the atmospheric geometric delay, the geometry shift and the geometric excess. We have defined corresponding atmospheric altimetry corrections necessary for unbiased altimetry retrievals. Using simulations, we examined the interferometric atmospheric delay for a range of typical scenarios, where it attained centimeter-level values at low satellite elevation angles ~ 5° for a 10-m high station. We found a linear and exponential dependence on reflector height and satellite elevation angle, respectively. A similar trend was found for the atmospheric altimetry correction, albeit with an amplified meter-level magnitude. The two delay components were similar near the horizon while the angular one vanished at zenith. For the altimetry correction components, both remained non-zero at zenith. We thus quantified the atmospheric bias in GNSS-R sea level retrievals.